Linker domain function predicts pathogenic MLH1 missense variants - London, James (Proc Natl Acad Sci U S A, 2021)
The pathogenic consequences of 369 unique human HsMLH1 missense variants has been hampered by the lack of a detailed function in mismatch repair (MMR). Here single-molecule images show that HsMSH2-HsMSH6 provides a platform for HsMLH1-HsPMS2 to form a stable sliding clamp on mismatched DNA. The mechanics of sliding clamp progression solves a significant operational puzzle in MMR and provides explicit predictions for the distribution of clinically relevant HsMLH1 missense mutations.